Allo-HSCT with TBI-based preconditioning for hepatosplenic T-cell lymphoma: two case reports and systematic review of literature - Chen, Can; Yang, Fan; Miu, Peiwen; Shi, Pengfei; Qian, Shenxian (Frontiers in Oncology, 2024)
Hepatosplenic T cell lymphoma allo-HSCT, allogeneic hematopoietic stem cell transplantation TBI, total body irradiation CR, complete remission TCR, T cell receptor EBV, Epstein-Barr virus CHOP, chemotherapy regimen consisting of cyclophosphamide, doxorubicin, vincristine, prednisone CR, complete remission PET-CT, positron emission tomography-computed tomography FACT, conditioning regimen consisting of TBI, Fludarabine, Cytarabine, and Cyclophosphamide HLA, human leukocyte antigen ICE, a chemotherapy regimen consisting of ifosfamide, carboplatin, and etoposide MTX, methotrexate MNC, mononuclear cell TNC, total nucleated cell CMV, cytomegalovirus DLI, Donor lymphocyte infusion PTCL, peripheral T cell lymphoma MAC, myeloablative preconditioning RIC, reduced intensity conditioning